Pelatihan Mendesain Lembar Kerja Praktikum Berbasis Predict-Observ-Explain Bagi Guru SMP - Nursa’adah, Euis; Firdaus, Mochamad Lutfi; Mayub, Afrizal (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2025)
Knowledge continues to evolve, requiring teachers to innovate, particularly in implementing the Kurikulum Merdeka (Independent Curriculum). Field observations indicate that many schools still struggle with its implementation, as they must tailor learning to students' individual characteristics. SMPN 03 Lebong in Bengkulu Province is one such school facing these challenges. Given these issues, an alternative solution is needed to support the independent implementation of the Kurikulum Merdeka. One possible approach is to provide training for teachers at SMPN 03 Lebong on designing learning activities and practical worksheets based on the Prediction, Observation, and Explanation (POE) model. This training follows the I-CARE design, which consists of five stages: Introduction, Connection, Application, Reflection, and Extension. As a result, teachers successfully developed six learning designs and practical guides based on the POE model, utilizing available tools and materials from their surroundings. This initiative enhances student-centered learning, aligning with the objectives of the Kurikulum Merdeka.